1994
DOI: 10.1007/bf01704700
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of one versus two bronchodilators in ventilated COPD patients

Abstract: The combination of both drugs is more effective than ipratropium bromide alone at the doses used in this study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0
5

Year Published

1996
1996
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(31 citation statements)
references
References 21 publications
(17 reference statements)
0
26
0
5
Order By: Relevance
“…A decrease in values of Rrs,max and Rrs,min occurs following bronchodilator administration in mechanicallyventilated patients [11,12,39,41,50].…”
Section: Assessment Of the Bronchodilator Responsementioning
confidence: 98%
See 2 more Smart Citations
“…A decrease in values of Rrs,max and Rrs,min occurs following bronchodilator administration in mechanicallyventilated patients [11,12,39,41,50].…”
Section: Assessment Of the Bronchodilator Responsementioning
confidence: 98%
“…Few investigators have examined the efficacy of bronchodilators in mechanically-ventilated patients [8,11,12,15,[38][39][40][41][42][43][44]. Early studies showed promising results following bronchodilator administration by a MDI [42][43][44], and yet the data were ignored for several years.…”
Section: Efficacy Of Bronchodilator Administered By a MDI In Mechanicmentioning
confidence: 99%
See 1 more Smart Citation
“…The combination of fenoterol and ipratropium bromide was found more effective than ipratropium alone in ventilated patients with COPD. (94) Combinations of inhaled corticosteroids (ICS) plus longacting b-agonist (LABA) (Advair, GSK, Research Triangle Park, NC; Symbicort Astra Zeneca, Wilmington, DE) are among the most effective and widely used treatments currently available for treatment of asthma. A combination of formoterol and budesonide used as a reliever as well as maintenance therapy may be employed for treatment of mild to moderate acute asthma exacerbations that could be managed at home.…”
Section: Bronchodilator Therapymentioning
confidence: 99%
“…Their use is recommended in COPD patients suffering from daily symptoms [73,74]. In ventilator-dependent patients, the combination of a β 2 -agonist with an anticholinergic was more effective than an anticholinergic alone to decrease airflow resistance [75].…”
Section: Pharmacological Treatmentmentioning
confidence: 99%